2019
DOI: 10.1111/mve.12392
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Lyme borreliosis spirochetes isolated from ticks in Serbia

Abstract: Spirochetes from the Borrelia burgdorferi sensu lato (s.l.). (Spirochaetales: Spirochaetaceae) species complex, including the causative agents of Lyme borreliosis, have been isolated from ticks, vertebrate reservoirs and humans. Previous analyses based on direct molecular detection in ticks indicated a considerable diversity of B. burgdorferi s.l. complex in Serbia. The present study aimed (a) to isolate borrelia strains from Serbia; (b) to determine their genotypic characteristics; and (c) to establish a coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…Research by Ćakićet al showed real-time PCR was conducted based on the hbb gene. Out of 36 isolated strains, 44.4% was identified as B. lusitaniae, 36.1% as B. afzelii, 13.9% as B. garinii and 5.6% as B. valaisiana [51]. An additional advantage of real-time PCR with melting curve analysis in comparison with the classic PCR is the possibility to observe increase product formation at each stage.…”
Section: Pcr Reaction-based Methodsmentioning
confidence: 99%
“…Research by Ćakićet al showed real-time PCR was conducted based on the hbb gene. Out of 36 isolated strains, 44.4% was identified as B. lusitaniae, 36.1% as B. afzelii, 13.9% as B. garinii and 5.6% as B. valaisiana [51]. An additional advantage of real-time PCR with melting curve analysis in comparison with the classic PCR is the possibility to observe increase product formation at each stage.…”
Section: Pcr Reaction-based Methodsmentioning
confidence: 99%
“…Thirteen borrelia strains: six B. afzelii , two B. garinii , three B. lusitaniae and two B. valaisiana, were selected from the collection of strains at the Institute for Medical Research, University of Belgrade, Serbia (4). Stock cultures of few passage borrelia strains had been stored at −80 °C, and subcultured for the study.…”
Section: Methodsmentioning
confidence: 99%
“…Borrelia strains may be isolated from different materials: human samples (skin, blood, cerebrospinal fluid, synovial fluid) as well as animal tissue or directly from ticks (3–5). Isolation and cultivation of B. burgdorferi s.l.…”
mentioning
confidence: 99%
“…complex. This complex is a diverse group of bacteria, distributed worldwide, and so far, the following species from ticks have been registered in Serbia: Borrelia lusitaniae, Borrelia afzelii, Borrelia garinii, Borrelia valaisiana, B. burgdorferi sensu stricto (s.s.), and Borrelia bavariensis (Čakić et al, 2019;Potkonjak et al, 2016b;Savić et al, 2010). In Europe and largely overlapping across the continent, the most commonly reported species are B.…”
Section: Borrelia Burgdorferi Sensu Lato (Sl) Complexmentioning
confidence: 99%
“…These spirochetes are predominantly transmitted on the European continent by ticks of the genus Ixodes (a principal vector is Ixodes ricinus), while small mammals, lizards, and birds have epidemiological significance as reservoirs of B. burgdorferi s.l. (Čakić et al, 2019;Steere et al, 2004). In general, the prevalence of B. burgdorferi s.l.…”
Section: Borrelia Burgdorferi Sensu Lato (Sl) Complexmentioning
confidence: 99%